Edema Paru Non Kardiak - Mulyadi Mulyadi (Universitas Syiah Kuala, 2010)
Abstrak. Edema paru terjadi apabila terjadi peningkatan laju filtrasi membran alveolo kapiler yang melebihi kapasiatas, Edema paru non kardiak adalah akumulasi cairan yang abnormal atau berlebihan dalam ruang interstitial dan alveolar paru akibat peningkatan penneabilitas mikro vaskular. Penyebab edema paru non kardiak sangat beragam, cidera paru akut, aspirasi dan inhalasi gas toksik, serta akibat infeksi. Penatalaksanaan utama ditujukan pada penyakit dasar, serta meliputi pengobatan non spesifik, pengobatan faktor pencetus, serta bertujuan untuk menjaga oksigenasi jaringan agar tetap adekuat. (JKS 2010,· l:37-42)Kata kunci : edema paru, non kardiak.Abstract. Pulmonary edema occurs when there is an increase speed of alveolo capillary filtration membrane that exceeds the capacity. The non-cardiac pulmonary edema is the accumulation of abnormal or excessive fluid in the interstitial and alveolar lung spaces due to the increasing of micro vascular permeability. The causes of non-cardiac edema pulmonary are very diverse which include acute lung injuries, aspiration and inhalation of toxic gases, and also due to infections. The main treatments are aimed to the basic diseases which include non- specific treatments, treatment of triggerer factors, and it is aimed to maintain tissue oxygenation as to make it remain adequate. (JKS 2010; 1:37-42)Keywords : non cardiac, pulmonary edema.